Pengaruh Motivasi, Kecerdasan Intelektual, Kecerdasan Emosional, Kecerdasan Spiritual, Terhadap Kinerja Guru SDN Kandangsapi 2 Kota Pasuruan - Novranti Aulia Rahmaudina; Abdul Kodir Djaelani; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThe purpose of this to analyze and explain the influence of motivation, intellectual quotient, emotional quotient, and spiritual quotient on the performance of teachers at SDN Kandangsapi 2 Pasuruan City. The dependent variable in this study is teacher performance. And there are 4 independent variables used, namely motivation, intellectual quotient, emotional quotient, and spiritual quotient. The population in this study were teachers of SDN Kandangsapi 2, Pasuruan City. The sample in this study was taken using census research techniques. The data collection method used is the method of distributing questionnaires to respondents. The data analysis technique used in this study is multiple linear regression. The results of the study stated that simultaneously the variables of motivation, intellectual intelligence, emotional intelligence, and spiritual intelligence had a significant effect on teacher performance. Partially the variables of motivation and intellectual intelligence have no significant effect on teacher performance, the emotional intelligence variable has a negative and insignificant effect on teacher performance, while spiritual intelligence has a significant effect on teacher performance. Keywords: Motivation, Intellectual Intelligence, Emotional Intelligence, Spiritual Intelligence and Teacher Performance.